Changing Undergraduate Medical Students’ Perception of Online Learning and Assessment During the Covid-19 Pandemic: a One Year Follow-up Study - Lim, Su-Yin; Lim, Yin Sear; Phyu, Khine Pwint; Lwin, Tint; Bhargava, Prabal (Malaysian Journal of Medicine and Health Sciences, 2022)
Introduction: Like most educational institutions, our medical school transitioned to online learning during the COVID-19 pandemic in March 2020. An initial survey of 192 undergraduate medical students conducted in June 2020 revealed a low acceptance of online assessments, lack of work-readiness, perception of online discussions as being inferior to face-to-face, and prevalent anxiety. Following this, we implemented pedagogic changes to encourage independent learning, improve patient contact, and increase social interactions between students. Methods: A follow-up study was conducted 12 months later in the same student population, excluding those who had graduated. The same 14-item anonymized survey questionnaire was administered, and comparisons were made between the follow-up and initial responses. Results: At follow-up, 45.6% of participants felt that online assessments can adequately and fairly assess students’ performance compared to the initial study (26.2%, p = 0.002). Participants at follow-up were generally more agreeable that discussion using an online learning platform was as effective as face-to-face learning compared to before (p = 0.017). Subgroup analysis showed that this was only true for Year 2 – 4 students. Year 5 students perceived online learning as less effective then face-to-face, reported lower confidence in their ability to apply their knowledge, and an increased in anxiety compared to before. Conclusion: While perception of online learning and assessment had improved at follow-up, the ramifications from restrictions to medical education over the past two years are now being felt most severely by the current final year students, emphasizing the importance of anticipating and addressing these concerns much earlier.